2017
DOI: 10.1038/s41598-017-14072-x
|View full text |Cite
|
Sign up to set email alerts
|

High-concentration hydrogen protects mouse heart against ischemia/reperfusion injury through activation of thePI3K/Akt1 pathway

Abstract: The study investigated the role of Akt1 through the cardioprotection of high-concentration hydrogen (HCH). C57BL/6 mice were randomly divided into the following groups: sham, I/R, I/R + HCH, I/R + HCH + LY294002 (PI3K inhibitor), I/R + HCH + wortmannin (PI3K inhibitor), I/R + LY294002, and I/R + wortmannin. After 45 min of ischemia, HCH (67% H2 and 33% O2) was administered to mice during a 90-min reperfusion. To investigate the role of Akt1 in the protective effects of HCH, mice were divided into the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The recent development of the H 2 generator has led to a gradual increase in the number of studies using high concentrations of H 2 . Inhalation of high concentrations of H 2 has been proved to ameliorate ischemia/reperfusion injury ( 36 , 37 ), endometriosis ( 38 ) and glyoxylate-induced calcium oxalate deposition ( 39 ) in animal models. Commercially available machines for inhalation of high concentrations of H 2 have also been used in patients ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The recent development of the H 2 generator has led to a gradual increase in the number of studies using high concentrations of H 2 . Inhalation of high concentrations of H 2 has been proved to ameliorate ischemia/reperfusion injury ( 36 , 37 ), endometriosis ( 38 ) and glyoxylate-induced calcium oxalate deposition ( 39 ) in animal models. Commercially available machines for inhalation of high concentrations of H 2 have also been used in patients ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the important role of AKT/GSK-3β in the treatment of PHLF by MSCs, we used an AKT inhibitor to activate GSK-3β by suppressing the phosphorylation of GSK-3β (Chen et al, 2017). We found that when GSK-3β was activated, the therapeutic effect of MSCs was eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic agents, including paclitaxel, cisplatin, bevacizumab, and olaparib (all from Sigma-Aldrich), diluted with DMSO, was intraperitoneally administered to mice. Anti-BTLA Ab (clone 6A6, Bio X cell) [28], anti-PD-1 Ab (clone RMP1–14, Bio X cell) [29], anti-PD-L1 Ab (clone 10F.9G2, Bio X cell) [30], anti-CD19 Ab (clone 1D3, Bio X cell) [31], LY294002 (Selleck Chemicals) [32], and BP-1-102 (Selleck Chemicals) [33] were also used for the following experiments.…”
Section: Methodsmentioning
confidence: 99%